Internal Audit: Rise and Development - Т. О. Kamenska (Статистика України, 2015)
Rise and current performance of internal audit is discussed. Key chronological phases of audit are defined by analyzing the development of international audit in the international context. Functions of international audit in corporations and the development of technologies used by auditors are taken as the chronology criteria. The five phases in which the notion “internal audit” was undergoing gradual evolution in the global theory